2021
DOI: 10.31925/farmacia.2021.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Fast Analytical Method for the Evaluation of the Encapsulation and Release Profile of Doxorubicin From Drug Delivery Systems

Abstract: Drug delivery systems are the most researched pharmaceutical formulation, representing promising tools in the treatment of cancer. Doxorubicin is an anti-tumour drug, widely used in malignant diseases, but with serious adverse effects. The aim of this study was to develop an analytical strategy for the evaluation of the encapsulation and release of this drug from delivery systems. The electrochemical oxidation process of doxorubicin has been studied using pencil graphite electrode by a fully optimized differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Drug release from PLA electrospun mats measured using the voltammetric method yielded a slightly lower release percentage compared to UV-VIS. The different sensitivities of the two methods may explain the difference in the results [ 31 ]. The presence of Hap in the nanofiber matrix resulted in a more complex release.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug release from PLA electrospun mats measured using the voltammetric method yielded a slightly lower release percentage compared to UV-VIS. The different sensitivities of the two methods may explain the difference in the results [ 31 ]. The presence of Hap in the nanofiber matrix resulted in a more complex release.…”
Section: Resultsmentioning
confidence: 99%
“…The applicability of the method was studied for examining the release of piroxicam [ 29 ], doxorubicin [ 18 ], naproxen [ 21 ], selegiline [ 30 ], etc. DPV is also a remarkable alternative method for the qualitative and quantitative investigation of drug dissolution [ 23 , 31 , 32 ]. The oxidation of the analyte and the corresponding current production are caused by voltage pulses of increasing amplitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Complexation of alginate with chitosan resulted in spectral displacement of carboxylic groups, with peak shifts from 1608 and 1429 cm −1 to 1618 and 1430 cm −1 , respectively. In the FT-IR spectrum of BSA/ALG/CHI MPs, the peak at 1528 cm −1 was indicative of N–H bending in amide groups in chitosan [ 58 ]. The corresponding peak in the range 1528–1534 cm −1 was attributed to C–N and C–N–H bending in chitosan [ 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…The protective effects of EVOO and VCO in combination were shown to be superior against oxidative stress in multiple organs in doxorubicin-treated rats [13]. The study showed that the combination could prevent the development of myocardial injury after doxorubicin injection [14]. Accordingly, the present study aimed to examine the protective effect of an EVOO and VCO combination in a ratio of 1:1, 1:2 and 2:1 in ISO-treated rats.…”
Section: Introductionmentioning
confidence: 91%